One-lung Ventilation for Thoracic Surgery: Current Perspectives. Issue 6 (November 2017) - Bernasconi, Filippo; Piccioni, Federico
One-lung ventilation (OLV) is an anesthesiological technique that is increasingly being used beyond thoracic surgery. This requires specific skills and knowledge about airway management, maintenance of gas exchange and prevention of acute lung injury. Sometimes maintaining adequate gas exchange and minimizing acute lung injury may be opposing processes. Parameters validated for OLV titration still have not been found, but a multimodal approach based on low tidal volume, end-expiratory pressure application and alveolar recruitment maneuvers is considered the best way to ensure protective ventilation and reduce lung damage. The purpose of this review is to analyze all these factors using the latest scientific evidence and the opinions of the most influential authors.